2016
DOI: 10.3390/v8100276
|View full text |Cite
|
Sign up to set email alerts
|

Cross- and Co-Packaging of Retroviral RNAs and Their Consequences

Abstract: Retroviruses belong to the family Retroviridae and are ribonucleoprotein (RNP) particles that contain a dimeric RNA genome. Retroviral particle assembly is a complex process, and how the virus is able to recognize and specifically capture the genomic RNA (gRNA) among millions of other cellular and spliced retroviral RNAs has been the subject of extensive investigation over the last two decades. The specificity towards RNA packaging requires higher order interactions of the retroviral gRNA with the structural G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 222 publications
0
32
0
Order By: Relevance
“…Unlike the lentiviruses that are assembled at the plasma membrane, MMTV is a Betaretrovirus that displays a type B morphology [ 16 ] during replication where intracellular virus particles can be observed. Little is known about how the virus particle is assembled and in particular, the molecular mechanisms of MMTV genomic RNA (gRNA) packaging—a process that allows the virus to incorporate two copies of its single-stranded RNA genome into the assembling virus particle [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Retroviral RNA packaging requires specific interactions between both the gRNA and viral structural proteins, in particular Gag [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the lentiviruses that are assembled at the plasma membrane, MMTV is a Betaretrovirus that displays a type B morphology [ 16 ] during replication where intracellular virus particles can be observed. Little is known about how the virus particle is assembled and in particular, the molecular mechanisms of MMTV genomic RNA (gRNA) packaging—a process that allows the virus to incorporate two copies of its single-stranded RNA genome into the assembling virus particle [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Retroviral RNA packaging requires specific interactions between both the gRNA and viral structural proteins, in particular Gag [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NC serves as the key player in selective gRNA packaging. It is a highly basic protein containing zinc finger motifs to facilitate protein-RNA interactions [ 17 , 35 ]. By conducting mutational analysis, it has been established that the Gag NC domain of number of retroviruses is the most vital protein domain involved in the gRNA packaging process [ 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a well-defined 5ʹ region of the murine leukemia virus (MLV) and some other retroviruses has been found to be required as well as sufficient for gRNA packaging, since inclusion of these sequences in heterologous non-retroviral RNAs facilitates the packaging of these ‘foreign’ RNAs into viral particles [14–17]. Furthermore, it is the presence of these structural motifs that explains the phenomena of co- and cross-packaging among retroviruses that have no relationship to each other [11]. For example, it has been long observed that specificity of packaging can be exchanged in many retroviruses by the substitution of packaging signals that have no sequence homology [1622].…”
Section: Introductionmentioning
confidence: 99%
“…The site of action of Zn 2+ is likely the HIV-1 NCp protein, a nucleic acid-binding protein composed of one or two cysteine-rich domains (CysteineX 2 CysteineX 4 HistidineX 4 Cysteine: CCHC motif) flanked by basic amino acids [136][137][138]. Moreover, NCp also regulates the trafficking of HIV-1 polyprotein Gag [139], HIV-1 genomic RNA (gRNA) dimerization [140,141], and generation of infectious progeny virion particles ( Figure 1) [142][143][144].…”
Section: Zinc (Zn 2+ )mentioning
confidence: 99%